TINJAUAN SISTEM RUJUKAN BPJS DI PUSKESMAS CIMAHI UTARA DALAM MENDUKUNG CAKUPAN PELAYANAN BPJS DI KOTA CIMAHI - Encep Hada; Suharto Suharto; Neni Rohaeni; Ayu Hendrati Rahayu (Jurnal TEDC, 2020)
Based on the results of a preliminary study, the authors found several factors that hindered referrals in the Cimahi Utara Public Health Center. The referral system procedure at Cimahi Utara Public Health Center did not work as it should because there were obstacles.The research method used in this study is a descriptive research method with a qualitative approach.Research results obtained by the author namelyfactors that hinder the BPJS referral system include lack of communication between referrals and referral purposes, socio-cultural conditions of the community that can slow down the referral process are: culture of negotiation, fear of being referred and treated and the process carried out with the help of a shaman, most people tend to access the nearest health care or perhaps the cheapest without regard to the competence of institutions or operators that provide services, the problem experienced by the puskesmas in serving public health inside the building or outside the building is the lack of energy, distance constraints are geographical factors. Suggestions to overcome the problem of the referral system procedure is that it is better for the referral officer to communicate more with the patient so that the patient knows the importance of the referral and the officer should also tell the referral flow to the patient so that the patient is not confused.